Spike-timing control by dendritic plateau potentials in the presence of synaptic barrages - Shai, Adam S.; Koch, Christof; Anastassiou, Costas A. (Frontiers in Computational Neuroscience, 2014)
Apical and tuft dendrites of pyramidal neurons support regenerative electrical potentials, giving rise to long-lasting (~ hundreds of milliseconds) and strong (~50 mV from rest) depolarizations. Such plateau events rely on clustered glutamatergic input, can be mediated by calcium and NMDA currents, and often generate somatic depolarizations that last for the time course of the dendritic plateau event. We address the computational significance of such single-neuron processing via reduced but biophysically realistic modeling. We introduce a model based on two discrete integration zones, a somatic and a dendritic one, that communicate via a long plateau-conductance. We show principled differences in the way dendritic versus somatic inhibition controls spike timing, and demonstrate how this could implement a mechanism of spike time control in the face of barrages of synaptic inputs.